THE EFFORTS TO IMPROVE STUDENT LEARNING RESULTS USING COOPERATIVE LEARNING MODELS OF TALKING CHIPS TYPES IN BIOLOGICAL DIVERSITY MATERIALS IN CLASS X MIA SENIOR HIGH SCHOOL 2 MEDAN ACADEMIC YEAR 2018/2019 - Rizki Annisa Ritonga; Zulkifli Simatupang; Nopita Sitompul (ISER (Indonesian Science Education Research), 2019)
This study aims to determine the increase in learning outcomes and student activities through the use of the Talking Chips type cooperative learning model on the subject matter of Biodiversity in class X MIA1 Medan 10 Senior High School T.P. 2018/2019. The research method is classroom action research, and the subject of this research is 35 students in class MIA1 as many as 35 people. The instrument used in the study was a test of learning outcomes in the form of pretest and posttest questions as many as 30 questions and student activity observation sheets. The results showed, based on the learning outcomes of the first cycle, the average score of pretest 40.6 increased to 68.6 in the posttest. In the second cycle, there was an increase from 62.8 to 74.5. In this study, data obtained from individual and classical learning completeness criteria, were as follows: as many as 30 of 35 students or 85.72% who scored above 70 or equal to 70, and 5 other students or equal to 14.28% scored below 70 Based on observations of student activities, the percentage of students who were active in the first cycle was 48.2% with the number of students 17 from 35 students, and students who were active in the second cycle by 80% with the number of students 28 out of 35 students. Keyword: learning outcomes, learning activities